Dynamics of Soil Mesofauna Population Cause by Addition Several Kind and Technique Application of Organic Materials on Oil Palm Weed Circle - Risky Ananda; T. Sabrina; Sarifuddin Sarifuddin (Universitas Sumatera Utara, 2017)
Population of soil mesofauna is strongly influenced by the availability of food sources in their environment. Food sources may include various types of organic materials. This research aimed to determine the effect of types and technique application of organic materials on weed circle towards the population of soil mesofauna. This research was conducted in Indonesia Oil Palm Research Institute (IOPRI) plantations Aek Pancur, Tanjung Morawa. This research was use factorial randomized block design. The first factor was the types of organic material, i.e. without organic material, litter, Empty Fruit Bunch (EFB), litter + T. harzianum and EFB + T. harzianum and the second factor was the technique application of organic materials i.e. spread in palm circle, put around the stand of palm and put on the threshold of palm circle. The results showed that in week 2, type of organic materials, technique application and both interaction was not affect soil mesofauna population, but in week 4, 6 8 and 12 type of EFB, technique application spread in palm circle and both interaction could increase the population of soil mesofauna. The highest population was on treatment B2A1 in week 12 (4106 ind m-2).